Monetary Policy and Macroeconomic Stability in Indonesia: A Systematic Literature Review - Agus Rohmat Hidayat (PT. Publikasiku Academic Solution, 2026)
Monetary policy has a strategic role in maintaining a country's macroeconomic stability, including Indonesia, by influencing inflation, interest rates, and economic growth. Global economic uncertainty and market volatility demand a deep understanding of the effectiveness of various monetary policy instruments and their impact on national economic stability. This study aims to explore how monetary policy affects macroeconomic stability in Indonesia through a systematic literature review (SLR) with a qualitative approach, to obtain comprehensive insights regarding monetary policy practices, challenges, and implications. The study uses a qualitative approach with SLR, reviewing national and international literature from 2010–2025 related to monetary policy, inflation, exchange rates, interest rates, and economic growth in Indonesia. The data were analyzed thematically to identify patterns, strategies, and implementation challenges of monetary policy, as well as its impact on macroeconomic stability. Findings show that monetary policy, including interest rate settings, liquidity intervention, and credit policy, plays an important role in maintaining Indonesia's economic stability. Adaptive implementation of monetary policy to global volatility increases market confidence, reduces inflation, and supports economic growth. The review results also identify challenges such as slow response to external changes, inter-institutional coordination, and limited policy instruments. Specifically, the findings recommend: (1) accelerating real-time economic monitoring systems to reduce institutional policy response lags; (2) establishing formal inter-institutional coordination frameworks between Bank Indonesia and the Ministry of Finance; and (3) expanding macroprudential instruments to complement conventional monetary tools, strengthening national economic resilience to global shocks.